Household Characteristics and Primary School Dropout Among Ugandan Children - Luyima, Jimmy; Rwakijjuma Komba, Leticia; Kamya , Willy (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2024)
This study explored the relationship between household characteristics and school dropout rates among primary school children in Uganda. Using secondary data from UWEZO Uganda’s 2015 survey, data was gathered from 16,373 children and 808 households across 112 districts. The study employed descriptive and inferential analyses, with Pearson correlation and linear logistic regression used to assess key household variables. Results showed that the gender and education level of the household head, the number of children, and meal frequency significantly influenced children's likelihood of dropping out of school. These findings underscore the importance of household well-being in ensuring children remain in school. The study suggests that, in addition to government efforts to promote gender equality, both parents should be equally engaged in their children’s education. It also advocates for family planning and food security campaigns to enhance school retention.